Analysis of non-polynomial systems using the sum of squares decomposition - Papachristodoulou, A; Prajna, S (2005)
Recent advances in semidefinite programming along with use of the sum of squares decomposition to check nonnegativity have paved the way for efficient and algorithmic analysis of systems with polynomial vector fields. In this paper we present a systematic methodology for analyzing the more general class of non-polynomial vector fields, by recasting them into rational vector fields. The sum of squares decomposition techniques can then be applied in conjunction with an extension of the Lyapunov stability theorem to investigate the stability and other properties of the recasted systems, from which properties of the original, non-polynomial systems can be inferred. This will be illustrated by some examples from the mechanical and chemical engineering domains. © Springer-Verlag Berlin Heidelberg 2005.